Ethnoveterinary data in Britain and Ireland: can native herbal medicine promote animal health? - Milliken, William (Ethnobotany Research and Applications, 2023)
Background: The use of plants, and occasionally fungi, to treat and cure animals or to supplement their feeding for livestock was widespread, globally. In some parts of the world this remains a key practice, but there is increasing use of veterinary pharmaceuticals which can have a negative effect on the wider environment. Meanwhile, traditional knowledge is being lost at a great rate, before it has been properly recorded and analyzed. Objective: This research analyses current and past ethnoveterinary use in Britain and Ireland and analyses the data within the context of medicinal uses, pharmacology, and other ethnoveterinary information collected in Europe. Methods: Ethnoveterinary data, collected from citizen science and literature, was analyzed by regional distribution (counties), use records (UR), and ATCvet classification. Results: A broad survey of the plants and fungi traditionally used to treat animals in the Britain and Ireland revealed 198 medicinal plants, principally for farm animals. This was a preliminary investigation, and although requests for current information were sent out in several formats though citizen science, the responses were relatively limited compared with other in situ ethnoveterinary surveys in other European countries. This may be partly due to the methodology, but probably also due to increased availability of modern veterinary medicines, the loss of traditional knowledge transfer between the generations, and concerns about animal safety, toxicity, and effectiveness with phytotherapy. The information reported here was compared with data collected in other countries and their known pharmacology. Some of the plant species cited are used more broadly within Europe for the same medicinal purposes, but in other cases the use appears to be restricted to Britain and Ireland. Conclusions: The information on ethnoveterinary uses recorded in this paper could assist with the development of novel biodegradable drugs and feed supplements for future animal management in a changing climate. With the increasing use of herbal lays and biodiversity grazing, and serious concerns about the over-use of veterinary medicines such as antibiotics and anthelmintics, and associated negative impacts on the environment and biodiversity, developing novel plant-based remedies may help to address some of the challenges. Further research on traditional ethnoveterinary knowledge in Britain and Ireland is timely, before the information has disappeared. Keywords: ethnoveterinary; plants; health; feed; livestock; anthelmintic; antimicrobial; traditional knowledge.